The 'Full Potential' of Uganda's Cotton Industry - Baffes, John (2012)
During the 1960s, Uganda was the largest cotton producer in sub-Saharan Africa. Attempts to revive the sector following its demise in the 1970s were unsuccessful in the 1980s and more effective in the 1990s. However, there is a sense that it still lags behind its full potential. Low quality of the cotton, lack of a domestic textile industry, and low use of purchased inputs due to lack of rural credit are identified as key constraints. This article argues that the fundamental problems are low profitability, which reflects the displacement of cotton by food crops, and the forced-labour conditions under which cotton was grown. It concludes that promotion of biotechnology and training cotton growers are two areas that should receive priority.